Community engagement in COVID-19 responses: Evidence from qualitative interface with community opinion leaders in Enugu, Nigeria - Agwu, Prince; Ugwu, Chinweoke Methodius; Eke, Chidera Florence (UI Scholars Hub, 2020)
Successful stories of community engagement existed during the Ebola disease outbreak in Liberia, indicating that a combination of government and community efforts are needed in addressing pandemics or epidemics. However, for communities to rise to the challenge of containing and combatting the spread of any disease, they must be communicated most effectively and supported by the government. Therefore, our study investigates how applicable successful community engagement has been in the charge against the Coronavirus disease 2019 (COVID-19) in Nigeria. Through telephone interviews, we sourced data from 12 community opinion leaders in Enugu State, Nigeria. After conducting a thematic analysis of responses, we discovered that the Nigerian government had several gaps in engaging the grassroots in the charge against COVID-19. These gaps comprise the lack of effective inclusion strategies of rural communities and the uneducated, weak accountability, poor database of citizens, weak accountability of security agents, weak primary healthcare system, and the dearth of grassroots-targeted communication. The effects of these gaps majorly manifested in the compromise and disregard of safety measures, which most likely put Nigeria at risk of increased cases of COVID-19 or poor response to disease outbreaks in the future. We concluded that the government must improve its accountability records while effectively interfacing with the grassroots during disease outbreaks and co-producing strategies.